Trait performance of F1 and F2 generations of rice (Oryza sativa L.) in relation to heterosis and inbreeding depression under saline soils - Hima, B P; Sumalini, K; Shiva, P G; Damodar, R C H; Sundaram, R M (Plant Science Today, 2026)
The extent of heterobeltiosis and economic heterosis of 24 F1s and inbreeding depression in 24 F2 generations, along with the parents, were raised in saline soils and estimated for ten characters under this study. Heterotic effects of 24 F1s revealed high and significant positive heterosis for grain yield in the cross combinations KPS 10640 × KPS 2874, KPS 10631 × KPS 2874, KPS 10642 × KPS 2874, KPS 10640 × RNR11718 and KPS 10633 × RNR11718, according to the results of better parent heterosis. The results of economic heterosis showed and high and significant positive heterosis for grain yield in the cross combinations KPS 10628 × CSR23, KPS 10640 × CSR23, KPS 10633 × RNR 11718, KPS 10651 × CSR36 and KPS 10640 × RNR11718. The range of inbreeding depression for grain yield was 4.09 % (KPS 10631 × CSR 23) to 42.45 % (KPS 10640 × RNR 11718). Twenty-one of the twenty-four crossings showed a substantial and positive inbreeding depression in F2 for grain yield. Not withstanding their grain yield, these F1s exhibited notable heterosis and inbreeding depression for a few key yield-contributing traits. This study showed that non-additive gene action is present in the inheritance of grain yield plant-1, along with several other yield-contributing traits and in the development of cultivars that can withstand salinity for long-term production.